Global Macroeconomic Announcements and Foreign Exchange Implied Volatility - Ishfaq, Muhammad; Qiong, Zhang Bi; Shah, Syed Mehmood Raza (International Journal of Economics and Financial Issues, 2017)
This paper examines the impact of the US and Chinese macro economic announcements on foreign exchange implied volatilities of SPX, VXFXI, BPVIX, JYVIX, and EUVIX from 2011 to 2016. The study indicates that implied volatility becomes significant and leads to the resolution of uncertainty on the day of the announcement but some part of information make significant revisions in the expectations of future volatility. However, no significant evidence found that uncertainty increases following an actual announcement. The EUVIX found more sensitive to US macroeconomic announcements and JYVIX to Chinese macro economic announcements. Most announcements related to Chinese manufacturing, industrial output and investments are found to have a significant effect on global implied volatilities. This study will help global and local investors to consider relevant announcements impact during portfolio evaluation and also monetary thinkers to devise a mechanism to reduce volatility around announcements. Keywords: Implied Volatility, Macroeconomic Announcements, Foreign Exchange JEL Classification: F31